Evaluation of the Glasgow Prognostic Score in patients receiving chemoradiotherapy for stage III and IV esophageal cancer. Issue 8 (1st December 2016) - Kimura, J.; Kunisaki, C.; Makino, H.; Oshima, T.; Ota, M.; Oba, M.; Takagawa, R.; Kosaka, T.; Ono, H. A.; Akiyama, H.; Endo, I.
Summary: High Glasgow Prognostic scores (GPSs) have been associated with poor outcomes in various tumors, but the values of GPS and modified GPS (mGPS) in patients with advanced esophageal cancer receiving chemoradiotherapy (CRT) has not yet been reported. We have evaluated these with respect to predicting responsiveness to CRT and long-term survival. Between January 2002 and December 2011, tumor responses in 142 esophageal cancer patients (131 men and 11 women) with stage III (A, B and C) and IV receiving CRT were assessed. We assessed the value of the GPS as a predictor of a response to definitive CRT and also as a prognostic indicator in patients with esophageal cancer receiving CRT. We found that independent predictors of CRT responsiveness were Eastern Cooperative Oncology Group (ECOG) performance status, GPS and cTNM stage. Independent prognostic factors were ECOG performance status and GPS for progression-free survival and ECOG performance status, GPS and cTNM stage IV for disease-specific survival. GPS may be a novel predictor of CRT responsiveness and a prognostic indicator for progression-free and disease-specific survival in patients with advanced esophageal cancer. However, a multicenter study as same regime with large number of patients will be needed to confirm these outcomes.